Net-mapping for low-emission food system development: Workshop on stakeholder mapping in Kapsabet, Kenya - Kibet, Walter; Habermann, Birgit (International Livestock Research Institute, 2023)
The CGIAR Initiative on Low-Emission Food Systems focuses on reduction of greenhouse gas (GHG) emissions while transforming food systems. It intends to work closely with key actors in the target countries, supporting them with new knowledge, information and tools to make robust evidence-based decisions as they confront challenges in food system transformation discourses, policy development and the reduction of GHG emissions. In Kenya, Nandi County has been selected as a site for a Living Lab for People (LL4P) on low-emission food system development.